Synthesis, characterization, and thermal rearrangement of zirconium tetraazadienyl and pentaazadienyl complexes - Gehrmann, Thorsten; Lloret Fillol, Julio; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2012)
Reaction of the zirconium dichloro complex [Zr(N2TBSNpy)Cl2] (1) with 1 molar equiv of ArNHLi (Ar = Mes, DIPP) yielded the zirconium imido complexes [Zr(N2TBSNpy)(═NDIPP)(py)] (2; N2TBSNpy = [(2-C5H4N)C(CH3){CH2NSi(CH3)2tBu}2]2-, DIPP = 2,6-diisopropylphenyl) and [Zr(N2TBSNpy)(═NMes)(py)] (3; Mes = mesityl). The imido complexes are converted to the tetraazadienido complexes [Zr(N2TBSNpy)(NDIPPN2NPh)] (4) and Zr(N2TBSNpy)(NMesN2NPh)] (5) by addition of phenyl azide, whereas the reaction of 2 or 3 with mesityl azide gave the alternative product 7, in which the azide is coupled with the CH activated ancillary tripod ligand. Reaction of 1 molar equiv of trimethylsilyl azide or 1-adamantyl azide with the previously reported hydrazinediido complex [Zr(N2TBSNpy)(═NNPh2)(py)] (9) at ambient temperature resulted in the formation of the five-membered zirconaacacycles [Zr(N2TBSNpy)(NTMSN3NPh2)] (10) and [Zr(N2TBSNpy)(NAdN3NPh2)] (11). Complex 11 was thermally converted into the diazenido complex 12 via loss of 1 molar equiv of molecular N2. The direct formation of the analogous side-on-bonded diazenido analogue 13 was observed upon reaction of 9 with 1 equiv of mesityl azide at ambient temperature. On the basis of 15N labeling and DFT modeling (DFT(B3PW91/6-31 g(d))) a mechanism for the reaction pathway leading to 12 and 13 is proposed.